Prevalence of urinary tract infection and associated risk factors among women in Sindhupalchowk district, Nepal - Paudel, Leela; Manandhar, Naresh; Sah, Saroj; Khadka, Sudesha; Neupane, Samikshya; Joshi, Sunil Kumar (International Journal Of Community Medicine And Public Health, 2018)
Background: Urinary tract infection (UTI) occurs in all age groups, more common in women due to short urethra and its close proximity to anus and vagina. UTI is defined as “microscopic finding of >10 pus cells/high power field (40x) in urine”. The purpose of the study is to find the prevalence of UTI and its association with various risk factors. Methods: An analytical cross-sectional study on prevalence of UTI was done among 260 women aged 15 years and above. Convenient sampling technique was used. Semi-structured questionnaire was designed to collect the data and urine sample was collected for routine and microscopic examination at the time of interview. Collected urine was sent, within 3 hours of collection. Results: The mean age of the respondents was 36.43±16.17 years. The prevalence of UTI among women aged 15 years and above was 36.9%.The most common symptom was frequency of micturition (35%) followed by lower abdominal pain (38.46%). There was significant association between frequency of micturition, burning micturition and lower abdominal pain with occurrence of urinary tract infection. On urinalysis, 96 samples were positive for pus cell; one sample showed blood, 16 samples showed ca-oxalate and 57 samples showed protein which determines the type of UTI. Smoking [COR-2.15, C.I-(1.12, 4.09)] and unavailability of toilet facility [COR-0.27, C.I-(0.08, 0.93)] were the significant risk factors for occurrence of UTI. Conclusions: There was high prevalence of UTI among women aged 15 years and above and association between smoking and unavailability of toilet facility and UTI was significant.